The link between independent acquisition of intracellular gamma-endosymbionts and concerted evolution in Tremblaya princeps - López-Madrigal, Sergio; Latorre, Amparo; Moya, Andres; Gil, Rosario (Frontiers in Microbiology, 2015)
Many insect species establish mutualistic symbiosis with intracellular bacteria that complement their unbalanced diets. The betaproteobacterium “Candidatus Tremblaya” maintains an ancient symbiosis with mealybugs (Hemiptera: Pseudococcidae), which are classified in subfamilies Phenacoccinae and Pseudococcinae. Most Phenacoccinae mealybugs have “Candidatus Tremblaya phenacola” as their unique endosymbiont, while most Pseudococcinae mealybugs show a nested symbiosis (a bacterial symbiont placed inside another one) where every “Candidatus Tremblaya princeps” cell harbors several cells of a gammaproteobacterium. Genomic characterization of the endosymbiotic consortium from Planococcus citri, composed by “Ca. Tremblaya princeps” and “Candidatus Moranella endobia”, unveiled several atypical features of the former’s genome, including the concerted evolution of paralogous loci. Its comparison with the genome of “Ca. Tremblaya phenacola” PAVE, single endosymbiont of Phenacoccus avenae, suggests that the atypical reductive evolution of “Ca. Tremblaya princeps” could be linked to the acquisition of “Ca. Moranella endobia”, which possess an almost complete set of genes encoding proteins involved in homologous recombination. In order to test this hypothesis, we performed comparative genomics between “Ca. Tremblaya phenacola” and “Ca. Tremblaya princeps” and searched for the co-occurrence of concerted evolution and homologous recombination genes in endosymbiotic consortia from four unexplored mealybug species, Dysmicoccus boninsis, Planococcus ficus, Pseudococcus longispinus and Pseudococcus viburni. Our results support a link between concerted evolution and nested endosymbiosis.